Influence of the family context on sleep disorders in children - Ana Luiza Paula de Aguiar Lélis; Maria Aneuma Bastos Cipriano; Maria Vera Lúcia Moreira Leitão Cardoso; Francisca Elisângela Teixeira Lima; Thelma Leite de Araújo (Universidade Federal do Ceará, 2014)
This study aimed to identify in the scientific literature the aspects related to the family context involved in sleep disorders in children. An integrative literature review was conducted in the databases: Lilacs, PubMed, Cinahl, Scopus and Cochrane, covering the period from 2007 to 2012, with the descriptors in Portuguese and English: transtornos do sono, família, criança, and sleep disorders, family, children. Thirty-four articles were identified, in which 46 aspects mentioned in the results were identified, highlighting the habits in the family sleep pattern and routine, cultural habits, socioeconomic status, and parental mood as the most frequent. Parents as family members and those responsible for directing the habits inherent in the family context have the key role in the sleep-wake process of the children.